Assessing the consequences of decentralizing biomedical research. Issue 1 (June 2019) - Bot, Brian M; Wilbanks, John T; Mangravite, Lara M
Advancements in technology are shifting the ways that biomedical data are collected, managed, and used. The pervasiveness of connected devices is expanding the types of information that are defined as 'health data.' Additionally, cloud-based mechanisms for data collection and distribution are shifting biomedical research away from traditional infrastructure towards a more distributed and interconnected ecosystem. This shift provides an opportunity for us to reimagine the roles of scientists and participants in health research, with the potential to more meaningfully engage in partnership across the research process. At the same time, these emerging practices present a potential to expose research participants to unanticipated and unintended consequences. Social norms and policy can help to mitigate these risks, but their development is often slow relative to the pace of technological advances and, as such, they can become reactive rather than prospective. As an alternative, the integrated development of data governance structures within technological advancements, supports their effective implementation, evaluation and evolution in a manner that can balance the benefits and risks of biomedical researcher in a decentralized ecosystem.